Quote:
Originally Posted by Vihzel
Calculations:
6÷2(1+2) =
6÷2(3) =
3*3 =
9
This is right.
6÷2(1+2) =
6÷2(3) =
6÷6 =
1
Wrong. To "see" it correctly, the equation should be written as (6/1)*(1/2)*((1+2)/1), which equals (6/1)*(1/2)*(3/1), which equals 9 no matter the order of the three "terms".
6÷2(1+2) =
6÷2+4 =
3+4 =
7
Now that's just stupid.

There you go.
It's been said before, but I tried to express it differently.
PS: I like to riddle my friends with this. I start with the first statement and proceed from there.
________a = b
________________(Premise)
_____a^2 = ab
________________(multiply each side by a)
a^2  b^2 = ab  b^2
__________(subtract b^2 from each side)
(a+b)(ab) = b(ab)
____________(factorization)
____(a+b) = b
_________________(simplification)
_____b+b = b
_________________(according to the premise)
______2b = b
_________________(addition...)